The importance of studying the images of architecture in miniature to recreate the appearance of the medieval baths of Shakhrisabz (Journal of Architectural Design, 2022)
In this article, miniatures by Kamoliddin Bekhzad and other artists of the Timurid and post-Timurid eras are considered as a source on the architecture of medieval baths. Depicting the external and internal structure and decoration of baths, they, along with historical sources and little-studied archival materials, can play an important role in restoring the former appearance of the interior and exterior of the medieval baths of Shakhrisabz.